Patient-independent variables affecting the assessment of aspirin responsiveness by serum thromboxane measurement - Petrucci, Giovanna; Rizzi, Alessandro; Cavalca, Viviana; Habib, Aida; Pitocco, Dario; Veglia, Fabrizio; Ranalli, Paola; Zaccardi, Francesco; Pagliaccia, Francesca; Tremoli, Elena; Patrono, Carlo; Rocca, Bianca (Thrombosis and Haemostasis, 2016)
The serum TXB2 (sTXB2) assay reflects the pharmacodynamics of platelet inhibition by low-dose aspirin. However, different studies reported variable sTXB2 values. sTXB2 assay requires whole blood incubation at 37 °C as a condition for optimal thrombin generation, arachidonic acid release and its metabolism by platelet cyclooxygenase-1 to form TXA2. Access to 37 °C incubation may be variably delayed, and different methods to quantitate sTXB2 may contribute to variable results between different Centers. We investigated whether delaying 37 °C incubation and/or analytical issues affect sTXB2 concentrations, biasing the assessment of aspirin responsiveness. Sixty-eight samples from 54 volunteers, on- and off-aspirin, were incubated at 37 °C immediately after sampling (reference sample) or after 5, 10, 15, 20, 30 or 60 minutes at room temperature (RT); 8 samples remained at RT 60 minutes, without subsequent incubation; 314 sera were measured by enzyme immunoassay (EIA) and liquid chromatography-tandem mass-spectrometry (LC/MS-MS) methods. sTXB2 concentrations decreased exponentially as a function of the delay before 37 °C incubation, ranging from 94 ± 11 % at 5 minutes to 23 ± 22 % of the reference sample after 60 minutes at RT. There was high agreement between EIA and LC/MS-MS. Moreover, we simulated the influence of a 15– or 30-minute delayed incubation on 300 sTXB2 measurements from previously-studied, aspirin-treated patients. Delayed incubation reduced the percentage of aspirin ‘non-responders’ by 22 % to 52 %, depending on the response threshold. In conclusion, a variable delay in the 37 °C incubation of blood samples may affect the assessment of platelet cyclooxygenase-1 inhibition by aspirin and confound the characterization of the determinants of aspirin responsiveness.
Keywords: Thromboxane B2; aspirin; cyclooxygenase-1; liquid chromatographytandem mass spectrometry; enzyme immunoassay